Lieno-Adrenal Shunt a Rescue for Porto-Systemic Decompression in 23-Year-Old Female - Ojha, Khagendra; Yadav, Prasun; Timilsina, Binaya; Mallik, Vipul Bhushan; Khatiwada, Sagar; Belbase, Narayan Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Extra hepatic portal vein obstruction is one of the commonest cause of portal hypertension and upper gastrointestinal bleed in the third world. Portal vein cavernous transformation is one of the hallmarks of EHPVO. Despite various lesser invasive interventional approaches for management of EHPVO, surgical shunts still play an important role in long term treatment of patients with EHPVO. Here we present a case of 23 years old female who presented to the OPD with complains of dull aching abdominal pain for a year which was insidious on onset and gradually progressive. The pain was non-radiating, localized to the left upper quadrant of the abdomen which aggravated on lying on the left side. She underwent lieno-adrenal shunt for porto-systemic decompression and management of EHPVO. This case aims to highlight the use of leino-adrenal shunt as a feasible alternative to Linton’s shunt.